PELATIHAN MENDESAIN BANNER MENGGUNAKAN TELEPON SELULER BAGI PELAKU UMKM DI RPTRA FLAMBOYAN MENTENG DALAM TEBET - Supriadi, Supriadi; Leonardi, Azka; Sumiyati, Sumiyati (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The Sahid University Jakarta community service team partnered with the management of the Flamboyan Child-Friendly Integrated Public Space (RPTRA) to hold banner design training using a cell phone with the Canva application. The aim of this community service is to provide knowledge and understanding about the importance of placing banners as promotional media, how to design banners and compose attractive and persuasive messages easily using a cell phone, so as to expand the culinary business market for women around this RPTRA. . This training activity was carried out in two stages, namely the first was providing material about the importance of making banners as a product promotion medium for women who operate micro-scale culinary businesses who live around the Flamboyan RPTRA. Second, practical assistance on how to design banners by the Fikom Usahid community service team, so that micro business women around the Flamboyan RPTRA, apart from understanding, can design banners and compose attractive messages, so that they can function as promotional media for their merchandise. After the evaluation was carried out, it could be stated that the training participants were very enthusiastic about participating in the training activities. Then, it can also be stated that the training in designing banners using cell phones was successful in increasing the knowledge and understanding of women who sell around the Flamboyan RPTRA. This is shown by the post test results being higher than the pretest results. Apart from that, at varying levels, training participants are able to design banners using cell phones, so that after the training the participants can design banners as promotional media for their merchandise, thereby increasing product sales.